(untitled) (Ustozlar uchun, 2024)
Аннотация: Green economy development has become an increasingly important topic in recent years, as countries around the world seek to address the challenges of climate change and environmental degradation. Uzbekistan, with its rich natural resources and growing economy, is no exception. The country has recognized the need to transition towards a more sustainable and environmentally friendly economic model, but faces various financial issues in doing so.